A novel approach for computing 3D mice distal femur properties using high-resolution micro-computed tomography scanning. (June 2019) - Mehadji, Brahim; Ahmed, Yoseph; Berteau, Jean-Philippe
Highlights: Segmentation using multi-thresholding and chondrocytes helps bone investigation. New 3D reconstruction of vascular Porosity, osteocytes lacunae and chondrocytes. Symmetric micromorphology has been found for medial and lateral condyles. Vessels tend to be perpendicular to the Calcified Cartilage before being tangential. Abstract: One of the most-scanned joints in preclinical animal models dealing with musculoskeletal pathologies is the mouse knee. While three-dimensional (3D) characterization of bone tissue porosity have previously been performed on cortical bone, it has not yet been comprehensively performed for the subchondral bone (SB) and the calcified cartilage (CC), which compose the subchondral mineralized zone (SMZ). Thus, it remains challenging to assess changes that occur in the SMZ of the mouse knee during pathologies such as osteoarthritis. One of the keys to addressing this challenge is to segment each layer to measure their morphologies, material properties, and porosity. Our study presents a novel approach for computing Tissue Mineral Density, 3D porosity, and the thickness of SB and CC in a mouse distal femur using High-Resolution Micro-Computed Tomography (HR-μCT). We have segmented the Vascular Porosity network, the osteocytes' lacunae of the SB, and the chondrocytes of the CC by using multi-thresholding and the percentage of chondrocytes porosity. Our results show a low intra- and inter-observer coefficient of variability. Regarding porosity and geometrical properties of both CC and SB, our results are within the range of the literature. Our approach opens new avenues for assessing porosity and vascular changes in the distal femur of preclinical animal models dealing with musculoskeletal pathologies such as osteoarthritis.